The Role of Administrative Control in Protecting Digital Records of the Administration - Nihad Sabri, Researcher. Theka; Majeed Jasim, Assist.Prof. Batool (Basra studies journal, 2025)
This study addresses the topic of “The Role of Administrative Oversight in the Protection of the Administration’s Digital Records,” emphasizing its relevance in the modern era of technological advancements, particularly with the widespread use of computers and the Internet. The misuse of these technologies has led to various unlawful acts affecting society from security, social, and economic perspectives, creating risks that were unforeseen when criminal laws were originally drafted, resulting in legislative gaps in addressing such offenses. Given the significant influence of digital platforms on individuals and communities, it has become essential to impose restrictions on these platforms through competent security and oversight authorities. These authorities are responsible for monitoring any website or publication that disrupts public order—the primary objective of the executive authority or government. Accordingly, the executive authority must exercise its role in supervising the digital environment in accordance with constitutional provisions governing rights and freedoms, as well as the laws and regulations regulating its functions. By utilizing digital technologies and specialized tools, these authorities work to prevent and address activities in the digital sphere that violate public order.